Decision making by manager in contractor's organization - Shakibabarough, Azin (2013)
There are many parties who were involved in the construction industry in Malaysia. Each party has their roles and responsibilities in ensuring that the projects completes on time, within the budget and the required quality. The parties have to make many decisions during the pre-tender stage, construction stage and commissioning stage. One of the main players in the construction industry is the contractors. Therefore, this study evaluates the decision made by managers at different levels in the contractors’ organization. The objectives of the study are to study the decision making process in the contractors’ organization, to investigate the types of decision made by the contractor, to evaluate the techniques of decision making in the contractors’ organization and to identify the problems faced by contractor’s in decision making. A total of 50 questionnaires were distributed but only 24 questionnaires were received duly answered. Interviews were also conducted on the respondents. The data collected were analyzed using statistical analysis and average index. From the finding, the decision making process involves 8 basic steps of which are definition of problem, determining the requirements that the solution to the problem must meet, establish goals that solving the problem should accomplish, identifying alternatives that will solve the problem, develop evaluation criteria based on the goals, select an effective decision-making tool, apply the tool to select a preferred alternative and check the answer to make sure it solves the problem. The techniques of decision making are brain storming, devil advocacy, Delphi technique and decision tree analysis. The problems faced by the contractor in decision making are financial constraint, lack of information and so on.